2019
DOI: 10.1111/caim.12303
|View full text |Cite
|
Sign up to set email alerts
|

Doing complexity leadership theory: How agile coaches at Spotify practise enabling leadership

Abstract: Complexity leadership theory (CLT) is about balancing formal and informal organization to leverage dynamics of Complex Adaptive Systems (CAS) and produce learning, creativity, and adaptation in organizations. Based on interviews with sixteen agile coaches (AC) at Spotify, this study examines how AC practice enabling leadership, a key balancing force in complexity leadership. Coaches practice enabling leadership by increasing the context‐sensitivity of others, supporting other leaders, establishing and reinforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 74 publications
3
80
0
4
Order By: Relevance
“…Research in other project industries has found horizontal leadership practices to boost team coordination (Carte et al 2006;Galli et al 2016;Hsu et al 2017;Sullivan et al 2015), increase the ability of organisations to cope with change (Chreim et al 2010;Kempster et al 2014; Rambe and Dzansi 2016) and enhance innovativeness and creativity (Hu et al 2017;Kakar 2017;Lee et al 2015;Sun et al 2016;Wu and Cormican 2016). Importantly, horizontal leadership has also been found to dramatically improve the effectiveness of agile approaches to project delivery in other industries (Bäcklander 2018;Dybå et al 2014;Li et al 2018;Moe et al 2015;Moe et al 2019;Xu and Shen 2018). is an organizational quality shared by all'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in other project industries has found horizontal leadership practices to boost team coordination (Carte et al 2006;Galli et al 2016;Hsu et al 2017;Sullivan et al 2015), increase the ability of organisations to cope with change (Chreim et al 2010;Kempster et al 2014; Rambe and Dzansi 2016) and enhance innovativeness and creativity (Hu et al 2017;Kakar 2017;Lee et al 2015;Sun et al 2016;Wu and Cormican 2016). Importantly, horizontal leadership has also been found to dramatically improve the effectiveness of agile approaches to project delivery in other industries (Bäcklander 2018;Dybå et al 2014;Li et al 2018;Moe et al 2015;Moe et al 2019;Xu and Shen 2018). is an organizational quality shared by all'.…”
Section: Discussionmentioning
confidence: 99%
“…They argue that as organizations rally in response to volatile industry demands, horizontal leadership should be implemented as it creates 'an atmosphere that consists of high levels of involvement, cooperation, shared understandings about team goals and purpose, and a sense of recognition'. Additionally, horizontal leadership has been demonstrated to be effective in situations where agile project management methods are employed, particular in software development (Bäcklander 2018;Dybå et al 2014;Li et al 2018;Moe et al 2015;Moe et al 2019;Xu and Shen 2018). For instance, Li et al (2018) consider integrated software development teams employing agile project management practices and highlight how 'shared leadership provides the opportunity for team members to utilize their expertise and identify the best solution for a problem'.…”
Section: Exploring New Possibilities For Construction Leadershipmentioning
confidence: 99%
“…An agile coach is often hired to help teams and companies adopt and take advantage of agile methods [5]- [7]. The role is also called a Scrum coach [8], kanban coach [9], lean coach [8], or devOps coach [10].…”
Section: Introductionmentioning
confidence: 99%
“…The agile coach role has become especially popular following the recognition of its success at Spotify [12]. Currently, more than 58,000 people on LinkedIn have "agile coach" as a job title.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation